2008
DOI: 10.1111/j.1475-6811.2007.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of humor use while resolving conflict in dating couples

Abstract: This research focused on whether affiliative and aggressive humor use was associated with relationship satisfaction and with greater perceived closeness, problem resolution, and emotional distress following a conflict discussion task. Ninety‐eight dating couples from a large Texas University participated in this research. Both partners independently completed questionnaires about their relationship perceptions, participated in a videotaped conflict resolution task, and then answered some additional questions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
111
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 35 publications
4
111
1
2
Order By: Relevance
“…In the current study, we focused on Martin and colleagues' (2003) aggressive and affiliative types of humor for two reasons. First, as described above, aggressive and affiliative humor are theorized to be the most relational forms of humor because they tend to be directed at others rather than at the self, and both influence daily personal and relationship well-being (Campbell et al, 2008). Second, we wanted to extend the dyadic conflict paradigm used by Campbell et al (2008) to a social support context.…”
Section: Types Of Humormentioning
confidence: 99%
See 4 more Smart Citations
“…In the current study, we focused on Martin and colleagues' (2003) aggressive and affiliative types of humor for two reasons. First, as described above, aggressive and affiliative humor are theorized to be the most relational forms of humor because they tend to be directed at others rather than at the self, and both influence daily personal and relationship well-being (Campbell et al, 2008). Second, we wanted to extend the dyadic conflict paradigm used by Campbell et al (2008) to a social support context.…”
Section: Types Of Humormentioning
confidence: 99%
“…First, as described above, aggressive and affiliative humor are theorized to be the most relational forms of humor because they tend to be directed at others rather than at the self, and both influence daily personal and relationship well-being (Campbell et al, 2008). Second, we wanted to extend the dyadic conflict paradigm used by Campbell et al (2008) to a social support context. Campbell and his colleagues found that greater use of aggressive humor in a conflict discussion (rated by observers) was particularly deleterious, even more so than affiliative humor was beneficial.…”
Section: Types Of Humormentioning
confidence: 99%
See 3 more Smart Citations